Dampak Elemen Visual Kemasan Minuman Jus Terhadap Persepsi Konsumen - Muyassar, Yasmin Mazaya Aini; Isnaini, Wiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Packaging is the first identifier that can attract consumers' attention to a product. Persuasive packaging design and specific visual design not only influence purchasing decisions, but also form a strong psychology of perception. In an increasingly competitive market, companies are required to create more creative packaging and build positive perception psychology. This study aims to analyze the influence of packaging design and its visual elements on the formation of preferences in terms of imagination of the flavor to be selected. To find out more, the research was conducted using a quantitative approach through an open online survey participated by 111 respondents, then divided into four age groups, which are 15-20 years old, 21-25 years old, 26-30 years old, and 30 years old and above. Then, the data was analyzed to identify consumption frequency, brand preferences, and consumer perceptions related to packaging design and the psychology of perception. Results show that the visual appearance of packaging is a dominant factor in purchasing decisions, especially among respondents aged 15-30. Perceptual psychology also plays a significant role, with brands such as Buavita being a top favorite due to its perceived trustworthiness and quality. However, there were concerns among the older age group regarding sugar content and nutritional value. Attractive packaging design and strong perceptual psychology can increase consumer preference for a product. Manufacturers are advised to continue to improve the visual elements of packaging as well as the transparency of information on labels to address consumers' health-related concerns.